Emerging topics in microvascular research: Advancing our understanding by interdisciplinary exploration. (6th December 2019) - Butcher, Joshua T.; Murfee, Walter L.; Stapleton, Phoebe A.
Abstract: Historically, major advances in microvascular research have been made by integrating physiology and bioengineering approaches. This Special Topics Issue focuses on providing a spotlight on emerging areas of microvascular research, showcasing how interdisciplinary collaborations and application of novel techniques can impact our understanding of tissue‐specific microvascular remodeling by integrating cell behaviors across scales. The authors in this issue investigate pericyte physiology, perturbations to uteroplacental blood flow, bone microvascular alterations in aging, molecular markers of revascularization, and microfluidic devices to mimic the lymphatic system. The articles highlight the continued importance of expanding our understanding of the microvascular system in health, and disease extends microvascular boundaries in the face of current paradigms, and illustrates how emerging leaders in the field are creating new scientific niches.